Asociación entre el volumen de residuo gástrico y complicaciones gastrointestinales y pulmonares en pacientes adultos con asistencia ventilatoria mecánica que reciben nutrición enteral - Narsiso Martinez, Helinking (2016)
Is there an association between gastric residual volume and; gastrointestinal and pulmonary complications in adults with mechanical ventilatory assistance who receive enteral nutrition? OBJECTIVES: To determine the association between gastric residual volume and; gastrointestinal and pulmonary complications in adults with mechanical ventilatory assistance who receive enteral nutrition. METHOD: The present study was observational - prospective. A total of 100 clinical histories checked from Trujillo’s Regional-Docents Hospital, the entire sample was obtained by exclusion criteria. The statistical analysis was done by Chi-Square test, regardless of criteria, with the significance level <0.05. RESULTS: Of the 100 patients for whom the data are collected, significant association wasn't found in the general characteristics evident. Also, it is found that: the percentage of patients with high volume gastric residual being the first day a total of 14% decreasing to the fifth day with the sixth day upturn. Finally, when analyzing each of the gastrointestinal complications (diarrhea, vomiting and abdominal distension) and pulmonary complications (ventilator associated pneumonia and aspiration pneumonia) with increased gastric residual volume wasn’t found statistically significant association. CONCLUSIONS: Gastric residual volume was ≥ 200 ml in 35% of patients and <200 ml in 65% of patients. Significant association wasn't found between increased volume of gastric residual and gastrointestinal and pulmonary complications. It was not found significant between increased gastric residual volume and gastrointestinal and pulmonary complications